Nutrition education to increase awareness about stunting among soon-to-be married couples in selected religion affair offices, Bekasi, West Java - Arindah Nur Sartika; Tri Marta Fadhilah; Afrinia Eka Sari; Guntari Prasetya; Noerfitri Noerfitri (Journal of Community Empowerment for Health, 2026)
Introduction: Nutrition education related to stunting is one of the strategies to tackle stunting incidence. A soon-to-be married couple is the right target to receive information about stunting, since they will be parents, especially a mother in the future. As it is known, the Religious Affairs Office has a pre-marriage training program, but not include nutritional sciences.Methods: A nutrition intervention consisting of nutrition education for men and women before marriage, to attend a mini lecture. The nutrition education program, including subjects related to marriage, is a pre-marriage education program from the selected religious affairs office in Bekasi. It aimed to increase nutrition knowledge, focusing on stunting prevention through family action. Participants were asked to fulfill nutrient adequacy for mothers as early as possible, before pregnancy, during pregnancy, and the lactating phase, as well as nutrient adequacy for infants during the first thousand days of life. They were also asked to ensure their health by joining the government’s program to visit the primary health service for antenatal care during pregnancy, and the integrated health center for growth monitoring after the baby is born. About 71 participants were recruited to do the pre-test, join the nutrition class, and finish the post-test.Results: Showed a double frequency of participants answering one hundred percent correctly during post-test, also most of the participants had an increased score in the post-test, p=0.000 (Wilcoxon signed-rank test). It showed that this program significantly increased participants’ knowledge about stunting.Conclusion: Nutrition education through simple lectures effectively improved knowledge about stunting. It is recommended to incorporate stunting topics into the pre-marriage education program as a preventive measure to reduce stunting.